High Cited Papers in Type 1 Diabetes Mellitus Immunotherapy: A Bibliometric Analysis of Global Publications During 1996-2023 - Vaishya, Raju; Gupta, Brij Mohan; Dhawan, Surinder Mohan; Singh, Yogendra; Bansal, Jivesh (DESIDOC Journal of Library & Information Technology, 2025)
The performance of global research in immunotherapy for type 1 diabetes mellitus (T1DM) was bibliometrically examined using 112 High-Cited Papers (HCPs) indexed in the Scopus database from 2016 to 2023. The HCPs were cited between 80 and 1019 times, with an average citation of 205.54. The lead country, institution, author, and journal were identified as the USA, University of California San Francisco, J.A. Bluestone, and Diabetes, respectively. Switzerland, Brigham and Women’s Hospital, USA, Q. Tang, and Annual Review of Immunology were found to be the most impactful countries, institutions, authors, and journals. The most frequent keywords were immunotherapy, insulin-dependent diabetes mellitus, and type 1 diabetes mellitus. It was observed that immunotherapy for T1DM as a research area has gained attention in global literature during the past decade from various countries and institutions. The research environment has predominantly been influenced by developed countries of North America and Western Europe. It is recommended to undertake large-scale randomised controlled trials and foster research partnerships between developed and developing nations to ensure long-term sustainability and a broader impact, globally.